The Effects of a Job Creation Scheme. Evidence from Regional Variation in Programme Capacities - Rainer Eppel (Austrian Institute of Economic Research (WIFO), 2014)
In direct job creation schemes, unemployed individuals at risk of permanent labour market exclusion are offered temporary subsidised employment in public or non-profit sector firms in combination with skills training and socio-pedagogical support. The main aim is to stabilise and qualify them for later re-integration into the regular labour market. Exploiting exogenous regional variation in population-group-specific programme capacities, I find evidence that such a job creation scheme is, on average, effective in providing a bridge to a regular job. The achieved integration is, however, often not stable. Successful participants face a high risk of once again becoming unemployed.
Keywords: 330